Stres Akademik Anak Usia Dini: Pembelajaran CALISTUNG vs. Tuntutan Kinerja Guru - Wulansuci, Ghina (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The success of education lies in the extent to which teachers use their abilities in educational practice. This study aims to analyze the academic stress in early childhood in Kindergarten institutions in Banjaran District. The research uses a qualitative approach using the case study. The subject of this research is a Kindergarten teacher in Banjaran District. Collecting data using observation and interviews. Analysis of research data using grounded theory. Test the validity of research data using triangulation of sources and techniques. The results of this study indicate that early childhood experiences stress in Banjaran District due to pressure from parents or guardians of students who want their children to be able to reading, writing, and counting. Principals and teachers have to fulfill the demands of parents or guardians of Kindergarten students in Banjaran District. In addition, the Principal of Kindergarten Schools in Banjaran District assigns various tasks to teachers. The findings of this study contribute to knowledge in the form of causes of early childhood academic stress and recommend early childhood education institutions to minimize stress in early childhood.